If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x) = (5x + 15) Reorder the terms: (6x) = (15 + 5x) Remove parenthesis around (15 + 5x) (6x) = 15 + 5x Solving (6x) = 15 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. (6x) + -5x = 15 + 5x + -5x Combine like terms: (6x) + -5x = 1x 1x = 15 + 5x + -5x Combine like terms: 5x + -5x = 0 1x = 15 + 0 1x = 15 Divide each side by '1'. x = 15 Simplifying x = 15
| 3x^2+10xy+3y^2=0 | | 8(7-x)(6+2)= | | 19728.14=x+(x*.0725) | | 8a-9a=23 | | 15x^2-3a=3-7a | | 14606.86=x+(x*.0725) | | 5/6-1/3n=p(5-2n) | | 3x-9x=43 | | 3x+9/2=9 | | n-16=2n+12+3x | | 9(8-7x)=-3 | | 7x+11=3x+727 | | s^2+5s=-18 | | 18305.5=x+(x*.0725) | | 36-x=-10x | | 4x-2x-2=6 | | (2x^2+5x)(25x^2-10-3)=125 | | X^5+2x^3-15x=0 | | 2g+5=15 | | n=-4m+9 | | x^3-6x^2-15x=0 | | xsquared-6x=27 | | -18-9d=7(8d+4) | | 2-y/12=15 | | y=2cos(3x)+3sin(3x) | | -25=-4+8(f+7) | | (5x)=(x+15) | | 2+5h=32 | | x^4+28x^2+75=0 | | 120=-16t^2+85t | | (x+5)=(2x-3) | | 5(-5)+-3=-23 |